Effect of Statistically Matching Equating Samples for Common‐Item Equating. Issue 1 (9th January 2021) - Lu, Ru; Kim, Sooyeon
Abstract : This study evaluated the impact of subgroup weighting for equating through a common‐item anchor. We used data from a single test form to create two research forms for which the equating relationship was known. The results showed that equating was most accurate when the new form and reference form samples were weighted to be similar to the target population. When the target population was a combination of the two equating samples and one sample was weighted to be similar to the other, the equating was less accurate but still much more accurate than equating with unweighted samples. Abstract : Report Number: RR‐21‐02